Wiredrawing hose and preparation process thereof
By using cycloolefin copolymer resin and fluoropolymer resin as water-blocking resin in the hose, and adding montmorillonite and waste paper-based cellulose nanocrystals as fillers, a wire drawing hose that can effectively prevent water and oxygen from penetrating is prepared, which solves the water and gas barrier problems in the storage of high-end daily chemical products, and realizes the recycling of waste paper materials.
Patent Information
- Application Number
- CN202411890240.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-03-28
AI Technical Summary
When storing high-end daily chemical products, existing hoses cannot adequately prevent the penetration of water and oxygen, causing the product to become thicker or deteriorate.
A wire drawing hose using a cycloolefin copolymer resin and fluoropolymer resin as water-blocking resin, combined with montmorillonite and waste paper-based cellulose nanocrystals as fillers, was prepared by a coextrusion process.
It achieves sufficient barrier to gas and moisture, significantly improves the water and gas barrier properties of the hose, meets the storage needs of high-end daily chemical products, and realizes the recycling of waste paper materials.
Smart Images

Figure BDA0005200480770000061 
Figure BDA0005200480770000071 
Figure BDA0005200480770000091
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of packaging materials, and more specifically, to a wire drawing hose and a preparation process thereof. Background Art
[0002] At present, many paste-like daily chemical products are stored in hoses. Such hoses are usually made of multi-layered sheets and have a certain degree of deformability. They can effectively protect the products from external pressure, extrusion and impact, and can easily achieve sealed storage of products. In addition, hoses are also portable, compact and lightweight. Through printing and heat transfer technology, personalized packaging can be achieved, which can fully meet consumers' needs for beauty and brand recognition.
[0003] In the related technology, there is a hose comprising a sheet body, which comprises a heat-sealing layer, a first adhesive layer, a barrier layer, a second adhesive layer and a support layer in sequence. The heat-sealing layer and the support layer are made of polypropylene, the first adhesive layer and the second adhesive layer are made of maleic anhydride grafted polyethylene, and the barrier layer comprises the following raw materials in parts by weight: 45-55 parts of polyethylene, 15-25 parts of oxygen-blocking resin, 15-25 parts of water-blocking resin, 1-3 parts of plasticizer, and 8-10 parts of compatibilizer. The oxygen-blocking resin is a terpolymer of ethylene / methyl acrylate / cyclohexene acrylic acid, and the water-blocking resin is a cyclic olefin copolymer.
[0004] With respect to the above-mentioned related technologies, the inventor believes that for high-end daily chemical products containing components that are sensitive to water and oxygen, the penetration of water and oxygen will cause the products to become thicker or deteriorate. In this case, the packaging needs to have extremely high water and gas barrier capabilities to prevent the loss and deterioration of the components. Although the hose in the related technology has certain water and gas barrier capabilities, it cannot fully meet the needs of high-end daily chemical products. Summary of the invention
[0005] In the related art, although the hose has certain water and gas blocking capabilities, it cannot fully meet the needs of high-end daily chemical products. In order to improve this defect, the present application provides a drawing hose and a preparation process thereof.
[0006] In a first aspect, the present application provides a wire drawing hose, which adopts the following technical solution: A wire drawing hose, the wire drawing hose is made of a wire drawing sheet material, the wire drawing sheet material is sequentially composed of a heat sealing layer, a first adhesive layer, a barrier layer, a second adhesive layer and a wire drawing support layer along the thickness direction, the barrier layer comprises the following components in parts by weight: 45-55 parts of polyethylene, 8-10 parts of a compatibilizer, 15-25 parts of an oxygen barrier resin, 15-25 parts of a water barrier resin, 8-10 parts of a filler, and 1-3 parts of a plasticizer, the water barrier resin comprises a cycloolefin copolymer resin and a fluorinated polyolefin, and the filler comprises montmorillonite and waste paper-based cellulose nanocrystals.
[0007] By adopting the above technical scheme, the present application selects cycloolefin copolymer resin and fluorinated polyolefin as water-blocking resin, and adds waste paper-based cellulose nanocrystals and montmorillonite as fillers. Fluorinated polyolefin has low surface energy and excellent oil and water repellency. While preventing water from invading the barrier layer, it can also limit the migration of water in the barrier layer. The addition of montmorillonite plays a heterogeneous nucleation role, promotes the crystallization of polyethylene, and improves the crystallinity of polyethylene. With the increase of polyethylene crystallinity, the regularity of polyethylene molecular chains increases. Under the coordinated cooperation of fluorinated polyolefin, it can more fully hinder the invasion and migration of water, which helps to improve the water-blocking performance of the wire drawing hose. On the other hand, the synergistic effect of fluorinated polyolefin and montmorillonite makes up for the disadvantages of waste paper-based cellulose nanocrystals on water-blocking performance, and waste paper-based cellulose nanocrystals have good gas barrier properties. Therefore, the wire drawing hose of the present application can fully achieve the barrier to gas and moisture, thereby overcoming the defects in the relevant technology and fully meeting the needs of high-end daily chemical products. In addition, the waste paper-based cellulose nanocrystals selected in this application are a kind of waste recycled material, which realizes the recycling of waste paper materials and helps to achieve green environmental protection.
[0008] Preferably, the fluorinated polyolefin is prepared according to the following method: (1) drying polypropylene for standby use; adding an initiator to styrene to dissolve it, and then adding dodecafluoroheptyl methacrylate to obtain a blend; (2) The blend is mixed with polypropylene to obtain a base material, the base material is added into an extruder for melt grafting, and a crude graft product is obtained after extrusion, drawing, cooling, pelletizing and drying, and the crude graft product is purified to obtain a fluorinated polyolefin.
[0009] By adopting the above technical solution, the present application first prepares polypropylene and the blend separately, then mixes the two as the base material, and performs melt grafting. During the melt grafting process, the initiator generates primary free radicals, and triggers the reaction of polypropylene macromolecules and grafting monomers, and alternately grafts fluorine-containing groups and styrene onto the polypropylene molecular chain, thereby obtaining fluorinated polyolefins.
[0010] Preferably, in the method for preparing the fluorinated polyolefin, the crude grafted product is purified as follows: the crude grafted product is added to xylene and heated under reflux until dissolved, then acetone is added for precipitation, the precipitate is filtered and dried, and the crude grafted product is purified to obtain the fluorinated polyolefin.
[0011] By adopting the above technical solution, the present application purifies the crude grafted product, removes impurities such as unreacted monomers and self-polymers produced by side reactions, and obtains relatively pure fluorinated polyolefins.
[0012] Preferably, in the method for preparing the fluorinated polyolefin, the weight ratio of polypropylene to dodecafluoroheptyl methacrylate is 1:(0.1-0.2).
[0013] By adopting the above technical solution, the present application optimizes the ratio of polypropylene to dodecafluoroheptyl methacrylate, and the grafting of fluorinated chain segments can be achieved within the above range.
[0014] Preferably, in the method for preparing the fluorinated polyolefin, the weight ratio of polypropylene to dodecafluoroheptyl methacrylate is 1:(0.15-0.2).
[0015] By adopting the above technical solution, the present application further optimizes the ratio of polypropylene and dodecafluoroheptyl methacrylate, which helps to fully realize the grafting of fluorine-containing chain segments.
[0016] Preferably, the water-blocking resin further comprises a modified cycloolefin copolymer, the components of which include a cycloolefin copolymer resin and mica flakes, and the weight of the mica flakes accounts for 2-4% of the total weight of the modified cycloolefin copolymer.
[0017] By adopting the above-mentioned technical scheme, the present application uses a modified cycloolefin copolymer containing mica sheets as a supplementary component of the water-blocking resin. In the process of preparing the modified cycloolefin copolymer, the molecular chains of the cycloolefin copolymer resin can be inserted into the layered structure of the mica sheets, and the mica sheets can increase the crystallinity of the cycloolefin copolymer resin through heterogeneous nucleation, thereby obtaining a modified cycloolefin copolymer with better water-blocking ability than pure cycloolefin copolymer resin, which helps to enhance the water-blocking performance of the drawn hose.
[0018] Preferably, the average particle size of the mica flakes is 35-45 μm.
[0019] By adopting the above technical solution, the present application optimizes the particle size range of mica flakes. Within the above range, the modified cycloolefin copolymer can effectively enhance the water-blocking performance of the drawn hose.
[0020] Preferably, the filler further comprises modified nano-silicon dioxide, and the modified nano-silicon dioxide is prepared according to the following method: (1) mixing ethanol and water, and then adding a silane coupling agent, and obtaining a silane-modified liquid after ultrasonic hydrolysis, and setting aside; drying the nano-silicon dioxide, and setting aside; (2) The nano-silica and the silane-modified liquid are mixed and heated in a water bath, and then centrifuged and separated, and the precipitate is washed and dried to obtain modified nano-silica.
[0021] By adopting the above technical solution, the present application uses a silane coupling agent to treat nano-silicon dioxide to obtain modified nano-silicon dioxide. The modified nano-silicon dioxide is easily dispersed in the barrier layer and can effectively play a heterogeneous nucleation role, reducing the free energy of the nucleation process, making the polyethylene molecular chain easy to adsorb nucleation and crystallization, and making the grains refined, thereby enhancing the crystallization performance of the composite material and improving the water-blocking effect of the wire drawing hose.
[0022] Preferably, the waste paper-based cellulose nanocrystals are prepared according to the following method: The waste paper is dried to constant weight, then mixed with sulfuric acid, and centrifuged after heating reaction. After the supernatant is separated, deionized water is added to the remaining solid for dialysis. After the dialysis, ultrasonic dispersion and centrifugal separation are performed, and the newly obtained supernatant is dried to obtain waste paper-based cellulose nanocrystals.
[0023] By adopting the above technical scheme, the present application uses waste paper as raw material, hydrolyzes it under the action of sulfuric acid, and then recovers waste paper-based cellulose nanocrystals from the hydrolysis product, thereby realizing the recycling of waste paper.
[0024] In a second aspect, the present application provides a process for preparing a drawn hose, which adopts the following technical solution.
[0025] A preparation process of a wire drawing hose comprises the following steps: (1) polyethylene, a compatibilizer, an oxygen barrier resin, a water barrier resin, a filler, and a plasticizer are weighed and mixed, and then melt-extruded and granulated to obtain a barrier material; (2) Weighing a heat-sealing layer raw material, a first adhesive layer raw material, a support layer raw material, a second adhesive layer raw material, and a wire drawing support layer raw material, and obtaining a wire drawing sheet after five-layer co-extrusion, cutting the wire drawing sheet, and welding and bonding the edges to obtain a wire drawing hose.
[0026] By adopting the above technical solution, the present application first prepares a barrier material, then co-extrudes the barrier material with materials of other layers to prepare a drawn sheet, and then uses the drawn sheet as a raw material to realize the preparation of a drawn hose.
[0027] In summary, this application has the following beneficial effects: 1. This application uses cycloolefin copolymer resin and fluorinated polyolefin as water-blocking resin, and adds waste paper-based cellulose nanocrystals and montmorillonite as fillers. The wire drawing hose of this application can fully achieve the barrier of gas and moisture, thereby overcoming the defects in the relevant technology and fully meeting the needs of high-end daily chemical products. In addition, the waste paper-based cellulose nanocrystals selected in this application are a kind of waste recycled material, which realizes the recycling of waste paper materials and helps to achieve green environmental protection.
[0028] 2. Apply to use modified cycloolefin copolymer containing mica flakes as a supplementary component of water-blocking resin. Mica flakes can improve the crystallinity of cycloolefin copolymer resin through heterogeneous nucleation, thereby obtaining modified cycloolefin copolymer with better water-blocking ability than pure cycloolefin copolymer resin, which helps to enhance the water-blocking performance of drawn hose.
[0029] 3. The method of the present application uses a silane coupling agent to treat nano-silicon dioxide to obtain modified nano-silicon dioxide. The modified nano-silicon dioxide is easily dispersed in the barrier layer and can effectively play a heterogeneous nucleation role, reducing the free energy of the nucleation process, making the polyethylene molecular chain easy to adsorb nucleation and crystallization, and making the grains refined, thereby enhancing the crystallization performance of the composite material and improving the water-blocking effect of the wire drawing hose. DETAILED DESCRIPTION
[0030] The present application is further described in detail below in conjunction with embodiments, preparation examples and comparative examples. The raw materials involved in the present application can all be obtained commercially.
[0031] Preparation Example of Fluorinated Polyolefin The following is an explanation using Preparation Example 1.
[0032] Preparation Example 1 In this preparation example, the fluorinated polyolefin was prepared according to the following method: (1) drying polypropylene for standby use; adding initiator DCP to styrene at a ratio of 1:10 to dissolve, and then adding dodecafluoroheptyl methacrylate to obtain a blend; in this step, the weight ratio of polypropylene to dodecafluoroheptyl methacrylate is 1:0.10, and the amount of initiator DCP is 5% of the weight of polypropylene; (2) mixing the blend with polypropylene to obtain a base material, adding the base material into a twin-screw extruder for melt grafting, and obtaining a crude graft product after extrusion, drawing, cooling, pelletizing and drying, adding the crude graft product into xylene, heating and refluxing until dissolved, then adding acetone for precipitation, filtering the precipitate and drying it to complete the purification of the crude graft product to obtain a fluorinated polyolefin; in this step, the temperature of each section of the twin-screw extruder is set to 165°C / 170°C / 175°C / 180°C / 180°C / 190°C / 190°C / 200°C / 190°C, and the screw speed is 70rpm.
[0033] As shown in Table 1, the difference between Preparation Examples 1-5 is that the weight ratio of polypropylene to dodecafluoroheptyl methacrylate is different.
[0034] Table 1 Weight ratio of polypropylene and dodecafluoroheptyl methacrylate sample Ratio Preparation Example 1 1:0.10 Preparation Example 2 1:0.12 Preparation Example 3 1:0.15 Preparation Example 4 1:0.18 Preparation Example 5 1:0.20 The preparation examples of modified nano-silica are described below using Preparation Example 6 as an example.
[0035] Preparation Example 6 In this preparation example, modified nano-silicon dioxide was prepared according to the following method: (1) ethanol and water were mixed in a volume ratio of 7:3 to obtain 1200 mL of ethanol aqueous solution, and then 5 g of silane coupling agent KH550 was added, and ultrasonic hydrolysis was performed at 80 kHz for 20 min to obtain a silane-modified liquid for standby use; the nano-silicon dioxide was dried and set aside; (2) After mixing 50 g of nano-silica and the silane-modified solution obtained in step (1), the pH value was adjusted to 10, and the mixture was heated in a water bath at 80° C. for 3 h, followed by centrifugation, and the precipitate was washed and dried to obtain modified nano-silica.
[0036] Preparation Example of Waste Paper-Based Cellulose Nanocrystals The following is an explanation of Preparation Example 7.
[0037] Preparation Example 7 In this preparation example, waste paper-based cellulose nanocrystals were prepared according to the following method: Waste A4 paper was dried at 70°C to constant weight, then mixed with 58wt% sulfuric acid solution at a solid-liquid ratio of 1:20, heated at 50°C for reaction for 90 minutes and then centrifuged. After separating the supernatant, deionized water was added to the remaining solid, and the paper was dialyzed to a pH of 7 after centrifugation. After the dialysis, ultrasonic dispersion was performed for 30 minutes, and then centrifuged again. The newly obtained supernatant was dried to obtain waste paper-based cellulose nanocrystals. Example
[0038] Examples 1-5 The following description is given by taking Example 1 as an example.
[0039] Example 1 This embodiment provides a wire drawing hose, which is made of a wire drawing sheet material, the thickness of the wire drawing sheet material is 300 μm, and a heat sealing layer, a first adhesive layer, a barrier layer, a second adhesive layer and a wire drawing support layer are sequentially distributed along the thickness direction according to a thickness ratio of 2:2:1:2:2. The heat sealing layer is bonded to the barrier layer through the first adhesive layer, and the barrier layer is bonded to the wire drawing support layer through the second adhesive layer. The surface of the wire drawing support layer is printed with a trademark pattern, and the surface has a wire drawing structure that provides an anti-slip effect.
[0040] The materials of the first adhesive layer and the second adhesive layer are both maleic anhydride modified copolymers, specifically maleic anhydride grafted polyethylene (Dow TY 1052H). The materials of the heat sealing layer and the drawing support layer are both polypropylene (SABIC PP 622L). The barrier layer includes the following components: 45kg polyethylene, 8kg compatibilizer, 15kg oxygen barrier resin, 15kg water barrier resin, 8kg filler, and 1kg plasticizer. The model of polyethylene is LDPE2426h, the compatibilizer is maleic anhydride modified copolymer (Mitsui QB516), the plasticizer is PE wax with an average molecular weight of 9000, the oxygen barrier resin is ethylene / methyl acrylate / cyclohexene acrylic acid terpolymer, model is Mitsubishi Chemical MB-2952; the water-blocking resin is composed of cycloolefin copolymer resin (TOPAS6013F-04) and the fluorinated polyolefin of Preparation Example 1 in a weight ratio of 1:1, and the filler is composed of montmorillonite and the waste paper-based cellulose nanocrystals of Preparation Example 7 in a weight ratio of 4:1.
[0041] This embodiment provides a preparation process of a wire drawing hose, comprising the following steps: (1) polyethylene, a compatibilizer, an oxygen barrier resin, a water barrier resin, a filler, and a plasticizer are weighed and mixed, and then melt-extruded and granulated to obtain a barrier material; (2) Weigh the raw materials for the heat sealing layer, the raw materials for the first adhesive layer, the raw materials for the support layer, the raw materials for the second adhesive layer, and the raw materials for the wire drawing support layer, and obtain a wire drawing sheet after five-layer co-extrusion, cut the wire drawing sheet, and weld and bond the edges to obtain a wire drawing hose; in this step, the five-layer co-extrusion sheet machine includes machine A, machine B, and machine C; machine A is a φ120 single screw extruder with a length-to-diameter ratio of 30:1, which is used to extrude maleic anhydride modified copolymer; machine B is a φ105 single screw extruder with a length-to-diameter ratio of 25:1, which is used to extrude polypropylene; machine C is a φ65 single screw extruder with a length-to-diameter ratio of 25:1, which is used to extrude barrier materials; set the thickness layer ratio in the control screen according to the thickness ratio: machine A 40%, machine B 40%, machine C 20%; set the extruder temperature: machine A 220℃±5℃, machine B 220℃±5℃, machine C 200℃±5℃, and the extrusion speed is 30m / min.
[0042] As shown in Table 1, the differences between Examples 1-5 mainly lie in the different raw material ratios of the barrier material.
[0043] Table 1 Raw material ratio of barrier material As shown in Table 2, the difference between Examples 5-9 is that the preparation examples of fluorinated polyolefins are different.
[0044] Table 2 Preparation examples of fluorinated polyolefins sample Preparation Example Example 5 Preparation Example 1 Example 6 Preparation Example 2 Example 7 Preparation Example 3 Example 8 Preparation Example 4 Example 9 Preparation Example 5 Example 10 The difference between this embodiment and embodiment 9 is that the water-blocking resin is composed of a cycloolefin copolymer resin modified cycloolefin copolymer and a fluorinated polyolefin in a weight ratio of 1:1:2. The modified cycloolefin copolymer is blended with a cycloolefin copolymer resin and mica flakes, the weight of the mica flakes accounts for 1% of the total weight of the modified cycloolefin copolymer, and the average particle size of the mica flakes is 60 μm.
[0045] Embodiment 11 The difference between this embodiment and embodiment 10 is that the weight of the mica flakes accounts for 2% of the total weight of the modified cycloolefin copolymer.
[0046] Example 12 The difference between this embodiment and embodiment 10 is that the weight of the mica flakes accounts for 3% of the total weight of the modified cycloolefin copolymer.
[0047] Example 13 The difference between this embodiment and embodiment 10 is that the weight of the mica flakes accounts for 4% of the total weight of the modified cycloolefin copolymer.
[0048] Embodiment 14 The difference between this embodiment and embodiment 13 is that the average particle size of the mica flakes is 45 μm.
[0049] Embodiment 15 The difference between this embodiment and embodiment 13 is that the average particle size of the mica flakes is 40 μm.
[0050] Example 16 The difference between this embodiment and embodiment 13 is that the average particle size of the mica flakes is 35 μm.
[0051] Embodiment 17 The difference between this embodiment and embodiment 16 is that the filler consists of montmorillonite, modified nano-silica and waste paper-based cellulose nanocrystals in a weight ratio of 2:2:1, and the modified nano-silica is prepared according to the method of preparation example 6.
[0052] Comparative Example Comparative Example 1 A hose is made of a sheet body with a thickness of 300 μm. The sheet body is provided with a heat sealing layer, a first adhesive layer, a barrier layer, a second adhesive layer and a support layer in a thickness ratio of 2:2:1:2:2 in the thickness direction. The heat sealing layer and the support layer are made of polypropylene (SABIC PP 622L), the first adhesive layer and the second adhesive layer are made of maleic anhydride grafted polyethylene (Dow TY 1052H), and the barrier layer comprises the following raw materials: 45 kg of polyethylene, 15 kg of oxygen barrier resin, 15 kg of water barrier resin, 1 kg of plasticizer and 8 kg of compatibilizer. The model of polyethylene is LDPE2426h, the compatibilizer is maleic anhydride modified copolymer (Mitsui QB516), the plasticizer is PE wax with an average molecular weight of 9000, the oxygen barrier resin is ethylene / methyl acrylate / cyclohexene acrylic acid terpolymer, model is Mitsubishi Chemical MB-2952; the water-blocking resin is cycloolefin copolymer resin (TOPAS6013F-04).
[0053] Comparative Example 2 The difference between this comparative example and Example 1 is that the filler component does not include montmorillonite.
[0054] Comparative Example 3 The difference between this comparative example and Example 1 is that the filler component does not include waste paper-based cellulose nanocrystals.
[0055] Comparative Example 4 This comparative example is different from Example 1 in that the water-blocking resin does not include fluorine-containing polyolefin.
[0056] Performance testing methods 1. Oxygen transmission rate test The oxygen barrier performance of the wire drawing hose was tested using an OX2 / 230 oxygen transmission rate tester in accordance with GB / T1038-2000, and the oxygen transmission rate of the tube body was tested under standard atmospheric pressure for 24 hours. The test temperature was 25°C, the test pressure was 0.1MPa, the relative humidity was 75%, the gas atmosphere was O2, and the test time was 24 hours. After the test, the oxygen transmission rate of Comparative Example 1 was used as a benchmark to calculate the ratio between the oxygen transmission rate of each embodiment and the comparative example and the oxygen transmission rate of Comparative Example 1, and the ratio was recorded as the oxygen relative transmission rate. The results are shown in Table 3.
[0057] 2. Water Vapor Transmission Rate Test The water permeability of the wire drawing hose under standard atmospheric pressure for 24 hours was tested using a 3 / 33MA type moisture permeator in accordance with GB / T26253-2010. The test temperature was 25°C, the test pressure was 0.1MPa, the relative humidity was 90%, the gas atmosphere was water vapor, and the test time was 24 hours. After the test, the water vapor permeability of the comparative example 1 was used as a reference to calculate the ratio between the water vapor permeability of each embodiment and the comparative example and the water vapor permeability of the comparative example 1, and the ratio was recorded as the relative water vapor permeability. The results are shown in Table 3.
[0058] Table 3 Test results Combining Examples 1-5 and Comparative Example 1 and Table 3, it can be seen that the oxygen transmission rate and water vapor transmission rate measured in Examples 1-5 are lower than those in Comparative Example 1, indicating that the wire drawing hose of the present application can fully achieve the barrier of gas and moisture, thereby overcoming the defects in the related art and fully meeting the needs of high-end daily chemical products. In addition, the waste paper-based cellulose nanocrystals selected in the present application are a waste recycled material, which realizes the recycling of waste paper materials and helps to achieve green environmental protection.
[0059] Combining Example 1 and Comparative Example 2 with Table 3, it can be seen that the oxygen permeability rate measured in Comparative Example 2 is close to that in Example 1, while the water vapor permeability rate is higher. This is because Comparative Example 2 cannot hinder the intrusion and migration of water through the combination of montmorillonite and fluorinated polyolefin, and the disadvantages of waste paper-based cellulose nanocrystals on water barrier performance are difficult to be fully overcome, resulting in a decrease in water barrier performance.
[0060] Combining Example 1 and Comparative Example 3 and Table 3, it can be seen that the oxygen permeability rate measured in Comparative Example 3 is lower, while the water vapor permeability rate is close to that in Example 1, indicating that montmorillonite can effectively prevent the intrusion and migration of moisture in the synergistic combination of fluorinated polyolefin, but due to the lack of waste paper-based cellulose nanocrystals, the gas barrier performance is poor.
[0061] Combining Example 1 and Comparative Example 4 with Table 3, it can be seen that the oxygen permeability rate measured in Comparative Example 4 is close to that in Example 1, while the water vapor permeability rate is higher. This is because Comparative Example 4 cannot hinder the intrusion and migration of water through the combination of montmorillonite and fluorinated polyolefin, and the disadvantages of waste paper-based cellulose nanocrystals on water barrier performance are difficult to be fully overcome, resulting in a decrease in water barrier performance.
[0062] It can be seen from Examples 5-9 and Table 3 that the water vapor transmission rates measured in Examples 7-9 are relatively low. This is because the fluorinated polyolefin prepared under the condition that the weight ratio of polypropylene to dodecafluoroheptyl methacrylate is 1:(0.15-0.2) can more effectively synergize with the filler, thereby improving the water barrier properties of the drawn sheet and the drawn hose.
[0063] Combining Example 9, Examples 10-16 and Table 3, it can be seen that the water vapor transmission rates measured in Examples 10-16 are all relatively low. This is because the mica flakes in the modified cycloolefin copolymer can improve the crystallinity of the cycloolefin copolymer resin through heterogeneous nucleation, thereby obtaining a modified cycloolefin copolymer with better water blocking ability than the pure cycloolefin copolymer resin, which helps to enhance the water blocking performance of the drawn hose. By analyzing the data rules of Examples 10-16, it can be seen that when the average particle size of the mica flakes is 35-45μm, and the weight of the mica flakes accounts for 2-4% of the total weight of the modified cycloolefin copolymer, the water blocking performance of the drawn hose is better.
[0064] It can be seen from Example 16 and Example 17 and Table 3 that the water vapor transmission rate measured in Example 17 is relatively low. This is because the modified nano-silicon dioxide is easily dispersed in the barrier layer and can effectively play a heterogeneous nucleation role, which reduces the free energy of the nucleation process, making it easy for the polyethylene molecular chain to adsorb nucleation and crystallize, and refine the grains, thereby enhancing the crystallization properties of the composite material and improving the water-blocking effect of the drawn hose.
[0065] The above embodiments are merely explanations of the present application and are not limitations of the present application. After reading this specification, those skilled in the art may make modifications to the embodiments of the present application without any creative contribution as needed. However, as long as they are within the scope of the claims of the present application, they are protected by the patent law.
Claims
1. A wire drawing hose, characterized in that: The drawn hose is made of a drawn sheet material, which comprises a heat-sealing layer, a first adhesive layer, a barrier layer, a second adhesive layer and a drawn support layer in sequence along the thickness direction. The barrier layer comprises the following components in parts by weight: 45-55 parts of polyethylene, 8-10 parts of a compatibilizer, 15-25 parts of an oxygen-blocking resin, 15-25 parts of a water-blocking resin, 8-10 parts of a filler, and 1-3 parts of a plasticizer. The water-blocking resin comprises a cycloolefin copolymer resin and a fluorinated polyolefin, and the filler comprises montmorillonite and waste paper-based cellulose nanocrystals.
2. The wire drawing hose according to claim 1, characterized in that: The fluorinated polyolefin is prepared according to the following method: (1) Drying the polypropylene for later use; adding the initiator to styrene to dissolve it, and then adding dodecafluoroheptyl methacrylate to obtain a blend; (2) The blend is mixed with polypropylene to obtain a base material, the base material is added into an extruder for melt grafting, and a crude grafted product is obtained after extrusion, drawing, cooling, pelletizing and drying, and the crude grafted product is purified to obtain a fluorinated polyolefin.
3. The wire drawing hose according to claim 2, characterized in that: In the method for preparing the fluorinated polyolefin, the crude grafted product is purified according to the following method: The crude grafted product is added to xylene and heated under reflux until dissolved, and then acetone is added for precipitation. The precipitate is filtered and dried to complete the purification of the crude grafted product to obtain fluorinated polyolefin.
4. The wire drawing hose according to claim 2, characterized in that: In the method for preparing the fluorinated polyolefin, the weight ratio of polypropylene to dodecafluoroheptyl methacrylate is 1:(0.1-0.2).
5. The wire drawing hose according to claim 4, characterized in that: In the method for preparing the fluorinated polyolefin, the weight ratio of polypropylene to dodecafluoroheptyl methacrylate is 1:(0.15-0.2).
6. The wire drawing hose according to claim 1, characterized in that: The water-blocking resin further comprises a modified cycloolefin copolymer, the components of which include a cycloolefin copolymer resin and mica flakes, and the weight of the mica flakes accounts for 2-4% of the total weight of the modified cycloolefin copolymer.
7. The wire drawing hose according to claim 6, characterized in that: The average particle size of the mica flakes is 35-45 μm.
8. The wire drawing hose according to claim 1, characterized in that: The filler also includes modified nano silicon dioxide, and the modified nano silicon dioxide is prepared according to the following method: (1) Mix ethanol and water, then add a silane coupling agent, and obtain a silane-modified liquid after ultrasonic hydrolysis, and set aside; dry the nano-silicon dioxide, and set aside; (2) The nano-silica and the silane-modified liquid are mixed and heated in a water bath, and then centrifuged and separated. The precipitate is washed and dried to obtain modified nano-silica.
9. The wire drawing hose according to claim 8, characterized in that: The waste paper-based cellulose nanocrystals are prepared according to the following method: The waste paper is dried to constant weight, then mixed with sulfuric acid, and centrifuged after heating reaction. After the supernatant is separated, deionized water is added to the remaining solid for dialysis. After the dialysis, ultrasonic dispersion and centrifugal separation are performed, and the newly obtained supernatant is dried to obtain waste paper-based cellulose nanocrystals.
10. The process for preparing a wire drawing hose according to any one of claims 1 to 9, characterized in that: The following steps are involved: (1) Weighing polyethylene, a compatibilizer, an oxygen barrier resin, a water barrier resin, a filler, and a plasticizer, mixing them, and then melt-extruding and granulating them to obtain a barrier material; (2) Weighing a heat-sealing layer raw material, a first adhesive layer raw material, a support layer raw material, a second adhesive layer raw material, and a wire drawing support layer raw material, and obtaining a wire drawing sheet after five-layer co-extrusion, cutting the wire drawing sheet, and welding and bonding the edges to obtain a wire drawing hose.